Composition dependent microstructure and optical properties of boron carbide (BxC) thin films deposited by radio frequency-plasma enhanced chemical vapour deposition technique. (January 2019) - Bute, A.; Jena, S.; Bhattacharya, D.; Kumar, S.; Chand, N.; Keskar, N.; Sinha, S.
Graphical abstract: Highlights: Bx C thin films deposited via PECVD shows high reflectivity ∼ 81% at soft X-ray wavelength. Films with stoichiometric variation obtained at different substrate self-bias values. Correlation between optical constants and film stoichiometry has been discussed. Tunability of optical band gap was observed with changing carbon content. Abstract: Bx C thin films were deposited on silicon (100) and sodalime glass substrates using Radio Frequency Plasma Enhanced Chemical Vapour Deposition (RF-PECVD) technique, at different substrate self-bias varying from -100V to -250V. Optical property, structure and stoichiometry of the films were determined by spectrophotometry, X-ray diffraction and proton elastic backscattering spectrometric measurements respectively to investigate the effect of film composition on microstructure and optical properties. Film refractive index at a typical wavelength of 400 nm increased from 1.87 to 1.97 on account of increasing packing density of the films with substrate self- bias. Decrease in direct and indirect optical band gap with increasing substrate self-bias, has been explained on the basis of compositional variation i.e. boron/carbon stoichiometric ratio. Finally, soft X-ray reflectivity in the wavelength range of 40 Å–360 Å has been measured to explore its potential for application as optical material in this region of electromagnetic spectrum.